Harmonisasi Kewenangan Bank Indonesia dan Otoritas Jasa Keuangan Terkait Penerapan Regulatory Sandbox dalam Inovasi Berbasis Fintech di Indonesia - Niluh Martiniasih; Deli Bunga Saravistha (Publikasi Indonesia, 2022)
The progress of technological innovation in the era of globalization was so quickly. The digital technologi gives special colour in the financial business sector. During the pandemic, a lot of people switch use online transactions because of the implementation of restrictions community activities system applicate by the government. Behind the high growth graph, it turns out that in practice financial tecnology (fintech) are reaping various polemics in the community. The lack of knowledge of digital financial literacy has resulted in many citizens being entangled in the dynamics of illegal fintech lending cases. The fintech requires Bank Indonesia and the Financial Services Authority carry out intensive supervision of the legality of digital financial innovation companies through the Regulatory Sandbox mechanism. This article uses normative legal research as a reference basis in determining legal procedures related to the polemic of Fintech-based innovation companies in Indonesia. The analytical method used is qualitative and described descriptively. The results of this study are to find out the harmonization of BI and OJK authorities through the implementation of the Regulatory Sandbox mechanism by establishing PBI No.19 /12 /PBI /2017 and POJK No. 13/ POJK.02/ 2018 as the legal basis for the legalization of fintech innovations before they are widely circulated in the community.